Sharing and Distinction in Biodiversity and Ecological Role of Bryozoans in Mediterranean Mesophotic Bioconstructions - Giampaoletti, Jacopo; Cardone, Frine; Corriero, Giuseppe; Gravina, Maria F.; Nicoletti, Luisa (Frontiers in Marine Science, 2020)
Bryozoan assemblages of three mesophotic habitats, recently found in the Adriatic and Ionian Sea, were investigated in terms of species composition and diversity, colonial growth forms and species ecological affinity, with the purposes to analyze variations and similarities between the different bioconstructions and to compare the mesophotic assemblages with those of other benthic habitats. Bryozoans came from three sites off the Apulian coast: Monopoli, 30-55 m depth where scleractinians are dominant, Otranto, 45-64 m depth and Santa Maria di Leuca, 45-70 m depth, where the bivalve Neopycnodonte cochlear is the main bioconstructor. A total number of 50 species of bryozoans were recorded, accounting for about 10% of the total number of Mediterranean species. Only few species were shared between the three sites, whereas a considerable pool of species was characteristic of each site. The β-diversity and Sörensen similarity analyses highlighted the highest similarity between the two southern sites, Otranto and Santa Maria di Leuca, in respect to northern site of Monopoli, in agreement with the hydrological pattern of the area. The encrusting zoarial type was the most abundant in each site and few species with erect, celleporiform and petraliform colonies were found. The Sörensen similarity, based on data of zoarial forms composition, revealed values considerably higher than those based on species composition, thus highlighting the similar ecological role played by the bryozoans in all the sites. Moreover, significant differences between the mesophotic bryozoan assemblages and those of other benthic Mediterranean habitats were highlighted, showing higher affinity with the coralligenous and detritic sciaphilic habitats. The relevant ecological role of bryozoans as binders in the bioconstructions of the Mediterranean mesophotic zone has been exhibited.